2009
DOI: 10.1523/jneurosci.3424-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Response Properties of Neocortical Neuron Ensembles: Multiplicative versus Additive Noise

Abstract: To understand the mechanisms of fast information processing in the brain, it is necessary to determine how rapidly populations of neurons can respond to incoming stimuli in a noisy environment. Recently, it has been shown experimentally that an ensemble of neocortical neurons can track a time-varying input current in the presence of additive correlated noise very fast, up to frequencies of several hundred hertz. Modulations in the firing rate of presynaptic neuron populations affect, however, not only the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 18 publications
6
71
0
Order By: Relevance
“…Because P-unit action potentials lock onto the EOD (Hagiwara and Morita 1963), their membrane time constant is likely to be shorter than a single EOD period (ϳ1 ms) and thus potentially explains the ability of the P-units to quickly follow such a mean-coded signal. Cortical neurons also have been shown to rapidly follow mean-coded signals (Boucsein et al 2009;Tchumatchenko et al 2011). A variancecoded transmission that was suggested for rapid signal transmission (Silberberg et al 2004) is therefore not required.…”
Section: Discussionmentioning
confidence: 99%
“…Because P-unit action potentials lock onto the EOD (Hagiwara and Morita 1963), their membrane time constant is likely to be shorter than a single EOD period (ϳ1 ms) and thus potentially explains the ability of the P-units to quickly follow such a mean-coded signal. Cortical neurons also have been shown to rapidly follow mean-coded signals (Boucsein et al 2009;Tchumatchenko et al 2011). A variancecoded transmission that was suggested for rapid signal transmission (Silberberg et al 2004) is therefore not required.…”
Section: Discussionmentioning
confidence: 99%
“…The linear response function R E to input current modulations of different frequencies has been studied theoretically (Brunel et al, 2001;Fourcaud-Trocmé et al, 2003;Richardson, 2007) and experimentally (Köndgen et al, 2008;Boucsein et al, 2009), whereas its equivalent in time R E is closely related to the Wiener kernel (Poliakov et al, 1997) and the STA current of the neuron (Paninski, 2006;Badel et al, 2008a) (see Appendix). For both LIF and EIF models, the response R E to modulated current is essentially a low-pass filter, the cutoff frequency of which decreases with increasing background synaptic noise.…”
Section: Response To Current Modulationsmentioning
confidence: 99%
“…It was shown that the onset rapidness could be an indirect measure of cut-off frequency (Fourcaud-Trocme et al 2003). Furthermore, the recent in vitro studies provided information about high cut-off frequencies of real neurons (Köndgen et al 2008;Boucsein et al 2009) and a recent theoretical work reported that smaller timescales at the AP onset help to reproduce such high cut-off frequencies (Wei and Wolf 2011). Combining these results, it can be concluded that very rapid onsets, i.e.…”
Section: A Neuron Model With Cooperatively Gating Na Channelsmentioning
confidence: 86%